Reproducing or Resisting Gender Norms? Daughters’ Constructions of Fathering by Tertiary-Educated Fathers - Corleis, Viktoria (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.